Resource Allocation in Socio-Ecological Systems: Implications for Sustainable Rangeland Management in Kenya - Mariara, Jane Kabubo (Annals of Arid Zone, 2016)
This paper explores resource allocation decisions in Kenyan rangelands. We analyze choice decision of the producer to enter or not to enter livestock production, and the determinants of the optimal herd size. We apply the Heckman two-stage estimation procedure to correct for selectivity bias in the livestock production. optimal income and optimal herd size process. The results show that tenure security, assets and location of the household are important determinants of the decision to hold livestock and the optimal stocking rates and incomes. We find no evidence of selectivity bias in the decision to hold livestock, but there is self-selection in participation in livestock production and the optimal stocking rates. Main barriers to sustainable range management are identified to include population pressure, institutional constraints and poverty. Strategies focusing on elimination of these barriers are recommended.